ANALISIS PERBUATAN YANG DAPAT DIKENAKAN SINGER MENURUT HUKUM ADAT KALIMANTAN TENGAH DALAM PERSPEKTIF HUKUM PERDATA - Putri, Yoke Shintia; Joni; Tasrifinoor (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2024)
The customary law still in effect in Central Kalimantan, particularly among the Dayak Ngaju tribe, serves as a means of social control and governance. This study employs normative legal research methods and qualitative research types with a statutory approach. In Dayak Ngaju customary law,